PENYELESAIAN SENGKETA PERBANKAN SYARIAH DI INDONESIA - Ridwan, Murtadho (MALIA: Journal of Islamic Banking and Finance, 2017)
The development of sharia banking and finance institutions is so fast,but in terms of laws and regulatory regulations are still left behind. Among the regulations that still need to be addressed is the regulation related to the settlement of dispute sharia banking business. Where in this case there are still juridical problems, namely the dualism of judicial authority in the settlement of Islamic banking disputes. The result of the study shows that the settlement of Islamic banking dispute in Indonesia can be done through two lines, both litigation and nonlitigation channels. Religious Courts are the competent jurisdiction to resolve Islamic banking disputes on litigation channels, while through non-litigation channels can be done through deliberation, banking mediation, shariah arbitration and judiciary within the General Courts. The National Shariah Arbitration Board (BASYARNAS) is the most strategic forum for resolving the dispute over sharia banking because BASYARNAS can resolve disputes quickly, simply, and at a low cost. Keywords:sharia,dispute,jurisdiction,litigation